Characteristics of Patients with Depression Among Pregnant Women and Postnatal Mothers at Community Health Centers in the Depok City Service Area in 2025 - Oksilia, Sonya; Purba, Evani (Jurnal Indonesia Sosial Sains, 2026)
Postpartum depression affects more than 1 in every 10 women within one year of giving birth. Other mental health symptoms that can occur during or after pregnancy include anxiety, panic attacks, and psychosis. This study aims to assess the characteristics of depressed patients in pregnant women and postpartum mothers at the Depok City Work Area Puskesmas by 2025. This study is a quantitative research using an analytical descriptive research design with the aim of describing the characteristics of depressive patients in pregnant women and postpartum mothers at the Depok City Regional Health Center totaling 1,368 people. Furthermore, data analysis using univariate analysis with a statistical test, namely the chi square test to determine the existence of a relationship between the data taken and the risk of depression. The results of the Chi-Square test showed a value of p = 0.016 (p < 0.05), so it can be concluded that there is a significant relationship between age and the incidence of depression in the respondents. The results of the Chi-Square test showed a value of p = 0.026 (p < 0.05), so it can be concluded that there is a significant relationship between education level and the incidence of depression in the respondents. There is a significant relationship between maternal age and education level and the incidence of depression in pregnant women.